The Urgency of PAI Teachers' Personalities in Developing Character Education at SMPN Pidie Regency - Khaidir, Khaidir; Amiruddin, Hasbi; Widyanto, Anton; Mahmud, Salami; Silahuddin (Al-Fikrah, 2025)
School is a place for learners to develop potential, attitudes, and emotions. Teachers as educators play the role of role models with their personality competencies. This study aims to determine the personality competence of Islamic Religious Education (PAI) teachers at SMPN Pidie Regency, describe the implementation of character education, and explain the relevance of teachers' personalities to the development of character education in the school. The method used is a field study with a qualitative descriptive approach, through interviews, observations, and documentation. The results of the study show that the personality competencies of PAI teachers at SMPN Pidie Regency include stability, maturity, and wisdom, with a responsible attitude, pride in being a teacher, and commitment to self-development. PAI teachers have a work ethic based on ukhrawi intentions, and show a polite, fair, and patient attitude. They have noble morals, which can be seen from honesty and patience in supporting students, and making assignments as worship. The implementation of character education is carried out by internalizing character values into compulsory subjects, such as PAI and PKn, and using analogies that are relevant to students' lives. In local content subjects, character values such as religiosity, confidence, and discipline are also instilled. The personality of PAI teachers is very relevant in the development of character education, where teachers with integrity and empathy become effective role models for students. The personality development of PAI teachers is an important step towards achieving holistic and sustainable character education in schools.